2014
DOI: 10.1371/journal.pone.0088690
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Topological Organization of Functional PET Brain Network with Normal Aging

Abstract: Recent studies about brain network have suggested that normal aging is associated with alterations in coordinated patterns of the large-scale brain functional and structural systems. However, age-related changes in functional networks constructed via positron emission tomography (PET) data are still barely understood. Here, we constructed functional brain networks composed of regions in younger (mean age years) and older (mean age years) age groups with PET data. younger and older healthy individuals were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
59
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(75 citation statements)
references
References 62 publications
14
59
1
Order By: Relevance
“…In this study, the range from 0.1 to 0.5 (i.e., 0.1 < S < 0.5, interval ¼ 0.01) was chosen to be the standard threshold sequence, as a previous study reported. 11 Then, the threshold sequence was applied to the adjacency matrix to generate 41 binarized network matrices for each subject. Figure 5(c) shows an example from one subject's data, revealing a spatial representation of nodes and edges from one binary matrix with a middle threshold (S ¼ 0.25).…”
Section: Cross-correlation To Generate Adjacency Matrixmentioning
confidence: 99%
See 4 more Smart Citations
“…In this study, the range from 0.1 to 0.5 (i.e., 0.1 < S < 0.5, interval ¼ 0.01) was chosen to be the standard threshold sequence, as a previous study reported. 11 Then, the threshold sequence was applied to the adjacency matrix to generate 41 binarized network matrices for each subject. Figure 5(c) shows an example from one subject's data, revealing a spatial representation of nodes and edges from one binary matrix with a middle threshold (S ¼ 0.25).…”
Section: Cross-correlation To Generate Adjacency Matrixmentioning
confidence: 99%
“…We focused on demonstrating our AVC by using a few major parameters affected by age effects in a previous study. 11 Specifically, a set of global parameters investigated were global network metrics, including (i) clustering coefficient (C p ), (ii) shortest path length (L p ), (iii) global efficiency (E g ), (iv) normalized clustering coefficient (γ), (v) normalized characteristic path length (λ), and (vi) small-world (σ). For the local parameters, we focused on the hub information, including (i) nodal degree, (ii) nodal efficiency, and (iii) betweenness centrality.…”
Section: Generating Brain Network Matrices Using Graph Theory Analysismentioning
confidence: 99%
See 3 more Smart Citations